MODIFIKASIMAKANAN TRADISIONAL BALI BERBAHAN DASAR AYAM SEBAGAI DAYA TARIKWISATA DI DESA MENGWI BADUNG - I Nyoman Tri Sutaguna (Institut Pariwisata dan Bisnis Internasional, 2017)
Â The study, entitled â€œModified Traditional Food made Basis Support Chicken For Tourism Industry in Mengwiâ€ againts the background by the recent development of world tourism with tourist from the massive shift of interest in tourist to the tourism ethnic. Traveler began to look for unique tours are very concerned with the original character of the local community. One of which is owned by the culinary tourist destination. The research was conducted through descriptive interpretative study that aims to identify the presence of both interms of culinary tourism: (1) The modification of traditional foods made from chicken, (2) Travelerâ€™s perception of the traditional foods, (3) Attempts a restaurant or dinner in developing traditional food, the most common data collection method is observation, questionnaires, interviews and documentation while the theoretical basis used is the theory of perception and marketing strategy.Modification process that served traditional food is traditional food made from chicken that has been modified as traditional betutu chicken, chicken betutu modification and crispy chicken, have some process modifications such as: (1) Seasoning, (2) Procesing, (3) Taste, (4) Presentation. Traveler have a positive perception of the traditional food made from chicken in Mengwi tourist area. Based on the results of research, an effort that is suitable for the development of culinary tourism in the village of Mengwi to see the existing constraints are combined with the advantages that exist in traditional food is offered to tourists in the village of Mengwi is as follows efforts to develop food product made from chicken both in terms of seasoning, processing, taste and presentation, and menu variations based chickens among other things: add a menu like the chicken for example by treatment with the way steam, braising, and roasted by changing some traditional recipe with modifications such as roast chicken in orange